Surgical extraction with photobiomodulation as an adjunctive modality in patients at-risk for medication-related osteonecrosis of the jaw: retrospective study - Gianluca Tenore; Ahmed Mohsen; Alessandro Del Vecchio; Gaspare Palaia; Federica Rocchetti; Lucia Borghetti; Giuseppe Vasile; Francesca Graniero; Umberto Romeo (BMC Oral Health)
Abstract Aim The study aims to retrospectively assess and share the experience of the use of photobiomodulation (PBM) as an adjunctive to surgical extraction in patients at-risk for medication-related osteonecrosis of the jaw (MRONJ) due to a treatment history with bone-modifying agents. Methods The department database and medical records were examined in the period between 2016 and 2023. The inclusion criteria were; at-risk patients for MRONJ with current or previous treatment with bone-modifying agents, with or without a history of antiangiogenic agents administration, who underwent single or multiple dental extractions, subjected to PBM preventive protocol, and without a diagnosis or history of MRONJ development. The PBM protocol consisted of four sessions, two sessions before the intervention and two sessions after the intervention. The PBM parameters (per session) were; total power of 0.6 W, time of 15 min, frequency of 30 kHz, and total energy of 577.4 J. Results A total of 62 patients (58 females and 4 males) fulfilled the inclusion criteria with a mean age of 67.5 years. Complete healing without the development of MRONJ was shown in 50 (80.65%) patients, and the development of MRONJ was shown in 12 (19.35%) patients. The statistical analysis revealed a higher risk of MRONJ in patients with a history of administration of zoledronic acid (p = 0.029) and in patients undergoing corticosteroid therapy (p = 0.039). While a lower risk was observed in patients in treatment for thyroid pathology (p = 0.055). Conclusions The majority of the included at-risk MRONJ patients showed complete healing after surgical extraction with the use of PBM as an adjunctive modality. Corticosteroid treatment as a systemic risk factor and zoledronic acid as a drug-related risk factor show significant associations with the development of MRONJ.